Morphological characteristics of the duodenal papilla magna tumors - O. Yu. Usenko; V. O. Kropelnytskyi; V. P. Shkarban; K. P. Tumasova; O. O. Pidopryhora (Клінічна хірургія, 2022)
Objective. Studying of morphological characteristics of the duodenal papilla magna malignant tumors on the own material of the Division of Pathological Anatomy and Cytology of the Shalimov National Institute of Surgery and Transplantology.